Application of a parallel genetic algorithm to the global optimization of medium-sized Au–Pd sub-nanometre clusters - Hussein, Heider A.; Demiroglu, Ilker; Johnston, Roy L. (The European physical journal. B, Condensed matter physics, 2018)
To contribute to the discussion of the high activity and reactivity of Au–Pd system, we have adopted the BPGA-DFT approach to study the structural and energetic properties of medium-sized Au–Pd sub-nanometre clusters with 11–18 atoms. We have examined the structural behaviour and stability as a function of cluster size and composition. The study suggests 2D–3D crossover points for pure Au clusters at 14 and 16 atoms, whereas pure Pd clusters are all found to be 3D. For Au–Pd nanoalloys, the role of cluster size and the influence of doping were found to be extensive and non-monotonic in altering cluster structures. Various stability criteria (e.g. binding energies, second differences in energy, and mixing energies) are used to evaluate the energetics, structures, and tendency of segregation in sub-nanometre Au–Pd clusters. HOMO–LUMO gaps were calculated to give additional information on cluster stability and a systematic homotop search was used to evaluate the energies of the generated global minima of mono-substituted clusters and the preferred doping sites, as well as confirming the validity of the BPGA-DFT approach.